Effects of Body Weight Strength Training on Cognitive Function and Quality of Life in Healthy Older People: A Systematic Review of Randomized Controlled Trials - Herrera-Valenzuela, T (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Objective: This systematic review evaluated the effects of body weight strength training (BWST) on cognitive function and health-related quality of life (HRQoL) in apparently healthy older people compared with active/inactive control groups. Methods: A literature search was conducted in six databases: PubMed, Web of Science, Scopus, ScienceDirect, EBSCOhost, and PsycINFO. The PRISMA, TESTEX, RoB 2, and GRADEpro tools were used to assess the methodological quality and certainty of evidence. The protocol was registered in PROSPERO (code: CRD42024623038). Results: Among the 27,241 records, 9 randomized controlled trials involving 682 (85% women) apparently healthy older people were included. Compared with the active/inactive control groups, the BWST resulted in significant improvements in orientation to place, language, visuospatial ability, processing speed, attention, and short-term memory. Within-group improvements were observed in general cognitive function and health-related anxiety scores in both the BWST and active control groups. The calculation and set shifting improved only within the BWST group. Conclusions: The individual results of the RCTs suggest that BWST may have potential effects on cognitive function and HRQoL in apparently healthy older people. Nevertheless, the certainty of evidence was insufficient to support definitive recommendations. Therefore, further high-quality studies are needed to establish solid conclusions. © 2025 by the authors.